New surgical realities: implementation of an enhanced recovery after surgery protocol for gynecological laparoscopy—a prospective study - Vilches-Jimenez, Jose Carlos; Tripiana-Serrano, Beatriz; Villegas-Muñoz, Emilia Carmen; Sánchez-Pérez, Belinda; Jiménez-López, Jesús Salvador (Springer Nature, 2021)
Multimodal rehabilitation allows optimization of functional recovery in surgery patients by reducing the postoperative stress and hospital stay duration, without increasing the morbidity and mortality. It is reportedly successful in other surgical disciplines, and guidelines for its application to gynecological surgery are available; however, most evidence for these guidelines is derived from observational and/or retrospective studies. Therefore, this study aimed to investigate the applicability of an enhanced recovery after surgery (ERAS) protocol in laparoscopic gynecological surgery and its influence on the postoperative stay, morbidity, mortality, and readmission, through a prospective approach. Methods: This prospective cohort study was performed on 90 patients who underwent laparoscopic hysterectomy for benign causes from October 2017 to October 2019. Patients in whom the ERAS (ERAS group, n = 30) and traditional (control group, n = 60) protocols were implemented were compared. All patients were followed for 6 months. Results: The groups were homogeneous and did not differ significantly with respect to the demographic characteristics (age, ASA score, body mass index), surgical indications, and surgery types. Adherence to the ERAS protocol was over 99%. The postoperative hospital-stay durations were 1.73 days (r = 1–3) and 2.97 days (r = 2–6) in the ERAS and control groups, respectively (p = 0.000). No significant intergroup differences were observed in the rates of complications and readmissions. Conclusions: The ERAS protocol is applicable in laparoscopic gynecological surgery and can be implemented with good adherence. This can allow optimization of patient recovery by reducing the hospital stay duration, without increasing the rates of morbidity, mortality, or readmission.
Keywords: Cuidados postoperatorios; ERAS protocol; Gynecology; Laparoscopic hysterectomy; Benign disease; Cohort study